Risk factors for female perpetrators of intimate partner violence within criminal justice settings: A systematic review. (July 2018) - Mackay, Jenny; Bowen, Erica; Walker, Kate; O'Doherty, Lorna
Abstract: There is a lack of understanding of the risk factors for female-perpetrated intimate partner violence (IPV) relative to men's IPV behaviours. Males can access offence-specific interventions in prison and on probation. However, depending on national criminal justice policies, female IPV perpetrators access general offending behaviour programmes only or offence-specific programmes that have been designed with male perpetrators in mind. The extent to which men's and women's treatment needs are similar or different is unclear. The aim of this systematic review was to synthesise what is known about the risk factors for IPV perpetration by women located within criminal justice settings to inform appropriate interventions for this group of offenders. Thirty-one studies met inclusion criteria and no factors meeting our definition of risk factor were identified. However, there were associations between IPV perpetration and experience of child abuse, substance use, borderline personality traits, attachment issues and experiencing trauma. It remains unclear what factors need to be targeted in interventions for female IPV perpetrators, although associations have pointed to possible predisposing factors. In order to improve the evidence base for IPV interventions, researchers need to clearly define the term 'risk factor', extending beyond reporting on prevalence only, and to increase understanding of the pathways to IPV perpetration among women. Highlights: We explored risk indicators of female IPV offenders within criminal justice system. No causal risk factors have been identified for women who perpetrate IPV. Some factors may be correlated with IPV perpetration e.g. experiencing child abuse. Protective factors did not feature in the studies we reviewed. The difference between the needs of women and men who perpetrate IPV is unclear.